Community Education on Coffee Pulp Utilization for the Benefits of Green Economy Improvement - Soetanto, Hendrawan; Aprilia, Rizka Muizzu; Huda, Asri Nurul; Ritonga, Azra Salsabila; Hendrawan, Viski Fitri (International Journal of Community Service Learning, 2023)
The rapid development of Bondowoso regency as coffee production has created serious problems on environmental pollution due to improper and unacceptable coffee pulp (CoP) dumping along the roadside and plantation areas. This study aimed at community education to process CoP into valuable feeed ingredients for ruminant animals and concomitantly reduce the environmental pollution. The methodological approach used a survey, focus group discussion and direct demoplot at the center of coffee farmer’s region at Sukorejo village, Sumberwringin sub-district.  The results showed that almost exclusively the coffee farmers had no prior knowledge on the utilization of CoP as feed ingredients for ruminant animals and the practice of CoP dumping along the roadside and plantation area was associated with the lack of manpower to handle it particularly during the peak harvesting time.The introduction of technology utilizing alkaline ammonia in the form of NaOH to treat CoP during  the demo plot activity revealed that the quality of CoP as represented by the crude protein content and the dry matter digestibility increased by 32.5 % and 63.4 %, respectively indicating that this new product can play a pivotal role as feed ingredients for formulation of ruminant animal’s ration. Additionally, this can be sold at higher price than CoP without treatment which is normally sold at 1,200 IDR/kg and hence it becomes an additional source of income.